2014
DOI: 10.5751/es-06793-190405
|View full text |Cite
|
Sign up to set email alerts
|

Can multicriteria assessment tools help build trust into organic products?

Abstract: ABSTRACT. In a continuously expanding, globalizing, and industrializing organic market, organic consumers confront increasing complexity in organic product representation, labeling, and information that challenges how they build trust in organic products. We present a conceptual framework to analyze how consumers might build and practice trust in the organic agrifood chain. We asked specifically about the role of multicriteria assessment tools (MCATs) for trust building. We identified three consumer trust type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 70 publications
0
7
0
3
Order By: Relevance
“…Rittenhofer and Povlsen's analysis therefore emphasizes the importance of Freyer et al (2014)'s conceptual framework to analyze how consumers might build and practice trust in the organic agri-food chain, with particular regard to the role of multicriteria assessment tools for trust building. They identify three consumer trust types: (i) uninformed and unreflective trust in labels; (ii) informed and reflective trust based on extensive information, control, and certification; and (iii) informed, engaged, and self-reflective trust based on close farmer-consumer relationships.…”
Section: Multicriteria Assessment and Sustainability Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…Rittenhofer and Povlsen's analysis therefore emphasizes the importance of Freyer et al (2014)'s conceptual framework to analyze how consumers might build and practice trust in the organic agri-food chain, with particular regard to the role of multicriteria assessment tools for trust building. They identify three consumer trust types: (i) uninformed and unreflective trust in labels; (ii) informed and reflective trust based on extensive information, control, and certification; and (iii) informed, engaged, and self-reflective trust based on close farmer-consumer relationships.…”
Section: Multicriteria Assessment and Sustainability Transformationmentioning
confidence: 99%
“…For instance, Schader et al (2014) shows the trade-off between different aspects of knowledge, such as scope vs. precision, in assessment tools, and Marchand et al (2014) investigate the different forms of assessment tools and types of knowledge needed for scientific monitoring vs. farm development. Different target groups differ in what form of knowledge they expect and use, and the informed consumer identified by Freyer et al (2014) is the most likely to be influenced by multicriteria assessments. Measuring weights given to different disciplines (Peano et al 2014) quantifies differences in emphasis of different types of knowledge and provides a method to reframe the same sustainability data in different ways for different audiences, but it does not reconcile the underlying perspectives and debates about which should take overall precedence in how food and fibre are produced.…”
Section: Prospects For Future Sustainability Assessmentmentioning
confidence: 99%
“…Others focus on trust in institutions (Chen 2008, de Jonge et al 2008. Freyer et al (2014) identified three types of consumer trust in organic products: uninformed organic consumers, informed organic consumers, and informed and engaged consumers. This classification establishes linkages between trust and consumers' motivation, habits, and perceptions; however, it is inadequate for understanding the transformation of different types of trust in a broader context where trust relationships are more complex and trust is placed in divergent trustees.…”
Section: The Conceptualization Of Trustmentioning
confidence: 99%
“…This classification establishes linkages between trust and consumers' motivation, habits, and perceptions; however, it is inadequate for understanding the transformation of different types of trust in a broader context where trust relationships are more complex and trust is placed in divergent trustees. Based on the identity of trustees and previous work by Edelenbos and Eshuis (2012) and Freyer et al (2014), we propose a categorization of trust as shown in Table 1. Table 1.…”
Section: The Conceptualization Of Trustmentioning
confidence: 99%
See 1 more Smart Citation